The first dynasty of the Sealand in Mesopotamia - Boivin, Odette (Studies in ancient near Eastern records, 2018)
Intro -- Preface -- Contents -- Tables and Figures -- Conventions and Abbreviations -- 1. Introduction -- 2. The Sealand I in Babylonian historiography -- 3. Geographical and chronological considerations -- 4. A political history of the Sealand kingdom -- 5. The Sealand I palatial economy -- 6. The Sealand I panthea and religious history -- 7. Conclusion -- Appendix 1: BKL A and Babylon I-Sealand I synchronism -- Appendix 2: Sealand I year names -- Appendix 3: Text numbers corresponding to Table -- Bibliography -- Indexes.